Impact of Alcohol on Outcomes in Hospitalized Major Trauma Patients: A Literature Review. Issue 2 (March 2016) - Leonard, Elizabeth Anne; Buckley, Tom; Curtis, Kate
Abstract : To critically appraise available studies investigating the impact of alcohol outcomes in hospitalized patients after major trauma. Outcomes included injury severity, mortality, complications, and hospital/intensive care length of stay. Data were sourced from MEDLINE, CINAHL, and SCOPUS databases. Abstracts were screened for inclusion/exclusion criteria with 15 articles appraised and analyzed based on in-hospital outcomes. Although alcohol intoxication is associated with a marginal increase in the incidence of in-hospital complications (sepsis and multiorgan failure), overall studies suggest it is not associated with longer intensive care or in-hospital length of stay. This literature review also demonstrated decreased mortality and injury severity in patients with traumatic brain injury. Further research is required to determine the reasons for these associations.